2012
DOI: 10.1016/j.fm.2011.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and assessment of potential risk factors of Gram-negative isolates associated with French cheeses

Abstract: The goal of this study was to identify at the species level a large collection of Gram-negative dairy bacteria isolated from milks or semi-hard and soft, smear-ripened cheeses (cheese core or surface samples) from different regions of France. The isolates were then assessed for two risk factors, antibiotic resistance and volatile and non-volatile biogenic amine production in vitro. In total, 173 Gram-negative isolates were identified by rrs and/or rpoB gene sequencing. A large biodiversity was observed with ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
72
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(84 citation statements)
references
References 71 publications
4
72
0
3
Order By: Relevance
“…Using a culture-based approach, Mounier et al (14) detected a similar "house" microbiota in a washed-rind cheesemaking plant, dominated by Debaryomyces hansenii, Corynebacterium spp., and Staphylococcus saprophyticus, suggesting that this same functional community may generalize across facilities producing similar styles of cheese. Several of the halotolerant Gammaproteobacteria detected on aging surfaces and cheeses in this study have been isolated previously from European washed-rind cheeses, including Pseudoalteromonas (50), Halomonas (50)(51)(52)(53), and Vibrio (49,52), so likewise appear to be part of the style-specific microbiome enriched by washed-rind processing techniques and likely play a role in the maturation phenomena of these cheeses. The coryneform Actinobacteria detected on aging-room and cheese surfaces, particularly in facility A, have likewise been isolated from washed-rind cheeses previously, including Brevibacterium (50)(51)(52)54), Corynebacterium (50)(51)(52)54), and Brachybacterium (50,54,55).…”
Section: Discussionmentioning
confidence: 59%
“…Using a culture-based approach, Mounier et al (14) detected a similar "house" microbiota in a washed-rind cheesemaking plant, dominated by Debaryomyces hansenii, Corynebacterium spp., and Staphylococcus saprophyticus, suggesting that this same functional community may generalize across facilities producing similar styles of cheese. Several of the halotolerant Gammaproteobacteria detected on aging surfaces and cheeses in this study have been isolated previously from European washed-rind cheeses, including Pseudoalteromonas (50), Halomonas (50)(51)(52)(53), and Vibrio (49,52), so likewise appear to be part of the style-specific microbiome enriched by washed-rind processing techniques and likely play a role in the maturation phenomena of these cheeses. The coryneform Actinobacteria detected on aging-room and cheese surfaces, particularly in facility A, have likewise been isolated from washed-rind cheeses previously, including Brevibacterium (50)(51)(52)54), Corynebacterium (50)(51)(52)54), and Brachybacterium (50,54,55).…”
Section: Discussionmentioning
confidence: 59%
“…FD differed from the other farms by its hygiene practices, which were not as stringent as in the other farms and could promote these species. The following species, less frequently detected on the surface of cow teats, were (13). Gram-negative bacteria may have a positive or negative effect on the flavor of cheeses, depending on their ratio in the microbial community (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Spoilage-related, psychrotrophic γ-proteobacterial sequences (Pseudomonas, Stenotrophomonas and Aeromonas) have been found in other artisanal cheeses (Masoud et al, 2011). Marinomonas,a halotolerant γ-proteobacterium, was present in artisanal cheeses (Coton et al, 2012), but no clear association between cheese spoilage and its presence was found in the literature. Halotolerant bacteria may be transferred to the cheeses by the salt (Ishikawa et al, 2007).…”
Section: Comparison Between Cheese-makers and Ripening Timesmentioning
confidence: 96%